Centros Educa Mais: um inédito viável na educação do Maranhão? - UTTA, Ádria Karoline Souza de Aquino (2022)
This Master’s Thesis is part of the research group “School, Curriculum and Teacher Training” of the Universidade Federal do Maranhão – UFMA (Federal University of Maranhão) and aims to analyze the teachers conceptions about Freirean Education expressed in the guiding documents of the Centros Educa Mais (Educa Mais Centers) of São Luís, from the perspective of understanding the materiality of the educational work they develop. It is a study based on the public schools struggle for the right to offer knowledge that provides mechanisms to face the Brazilian contextual challenges that imply the education developed at the Educa Mais Centers in Maranhão. In this sense, we adopted the category of the Unpublished Viable found through our immersion in Paulo Freire’s theoretical frameworks, as it is expressed as the production of knowledge and promotion of social transformations that were formerly utopian in educational practices. To carry out the research, we used a qualitative approach, using instruments and techniques of bibliographic and documentar research, focus group and questionnaire, the last one being used to build the profile of the subjects. Data analysis and treatment were performed using Bardin’s Content Analysis (2006) which allows the deduction and inference to the data collected in the different analysis paths. The study was carried out in two Educa Mais Centers in the city of São Luís with 20 subjects. The theoretical and methodological references that supported the discussion on comprehensive education are supported by authors such as Cavaliere (2002, 2007), Coelho (2009, 2010), Gadotti (2009), Moll (2014) and Teixeira (1994); on Freirean Philosophy, we rely on Gadotti (1996, 2019), Haddad (2019), Streck, Redin & Zitkoski (2010) and Paulo Freire (1979, 1986, 1996, 2000, 2001, 2003, 2017, 2018); in the methodological approach, we anchored ourselves in the theoretical contribution of authors such as Bardin (2006), Bonfim (2008), Gatti (2005), Gondim (2011) and Minayo (2007; 2010). Allied to the referenced studies, we resorted to the documents that guided the implementation of the Educa Mais Centers in the state of Maranhão and the pedagogical work of the teacher, namely: Pedagogical Proposal for the Full-Time Schools of the State of Maranhão (2017); Law no. 10,995 of March 11, 2019, which establishes the educational policy “Escola Digna”; State Education Plan (2014-2024) – Law no 10,099; Ordinance no 1145 of October 10, 2016 and the Notebooks of the Escola da Escolha Pedagogical Model (2016). The research revealed to us that Paulo Freire’s philosophy is contained in the genesis of the integral education policy of the State of Maranhão and underlies the documents that guide the practice in the Educa Mais Centers, which shows an “Unprecedented Viable” in the education of the state; It also showed us that teachers conform to the Freirean philosophy expressed in these documents and try to follow this perspective, but, despite this, the materiality of work is submitted to business logic with processes and control instruments that absorb time at school and prevent the development of a pedagogical work that is coherent with Paulo Freire’s perspective in its entirety.